Guarantee the Confidentiality of Medical Data for Covid-19 Patients - Rosita, Riska; Rizky, Agusta Pinta Kurnia; Salsabila, Rara Nur (Poltekkes Kemenkes Riau, 2023)
Hospitals as health services are obliged to maintain the confidentiality of patient medical information. Facts circulating in the community, and the identity of Covid-19 patients is being disseminated in order to track or trace the closest contacts or other people's contacts. The purpose of this study is to analyze the limits of what medical information on Covid-19 patients can be disclosed by the health service in fulfilling requests from interested parties, as well as the procedures for disclosing Covid-19 patient information in guaranteeing confidentiality aspects. The research method is descriptive using a cross-sectional survey design approach. The results showed that there were 3 types of medical information for Covid-19 patients that could be disclosed, namely: (1) a Negative Covid-19 certificate, (2) a Diagnostic certificate, and (3) submission of insurance forms for replacement purposes. The conclusion is that all applications for a Medical Certificate, whether a Covid-19 case or not, are required to fill out a Statement of Release of information, and third parties are required to include a Power of Attorney for the Release of Information and a photocopy of identity.